Knowledge About Intake and Output Documentation among the Nursing Staffs of Dhulikhel Hospital - Gyawali, Susmita; Laxmi Bajracharya, Siddhi (Nepalese Medical Journal, 2022)
Introduction: Documentation of intake and output is written or electronically generated information about client’s all the fluid that goes into and is eliminated from the patient’s body. Fluid balance monitoring and documentation is a challenging area in nursing practice, since patients’ management plan for surgery, renal, cardiac, and acute gastrointestinal disease depends on the nurse’s documentation, it is hence of medical and ethical importance. Thus, we intend to assess the knowledge about intake and output documentation among the nursing staff of Dhulikhel Hospital. Materials and Methods: A simple descriptive cross-sectional study was conducted among the 100 nursing staff using the stratified random technique. A self-administered questionnaire was used. T-test was used for comparison. Respondents’ knowledge was analyzed by using the software SPSS 16.0. Results: This study showed the mean knowledge percentage score of nursing staff working in Dhulikhel Hospital was 59.25%. There was a significant difference in mean knowledge score between respondents with a Certificate Level in Nursing and Bachelor level (p= 0.008), between respondents of Surgical Units and Non-Surgical Units (p= 0.001). Other variables like personal experience and previous in-service or education on intake and output documentation did not have any significant difference in mean knowledge score. Conclusion: The findings of the study suggested that the knowledge regarding intake and output documentation among nursing staff was average.